Estructura horizontal de las especies comerciales del bosque de terraza baja de la Comunidad Nativa Puerto Arce. distrito de Emilio San Martín y Tapiche. Loreto – Perú. 2022 - Gordon Soria, Christian Andre (2023)
The study was carried out in the low terrace forest of the Puerto Arce native community. District of Emilio San Martín and Tapiche. Loreto-Peru. 05 species, 04 botanical families and 758 trees were registered. It was considered that the Moraceae and Rubiaceae families are the most predominant with nine Moraceae species (480 species), followed by the Rubiaceae family (244 species). The Capinurí species is the most ecologically important in that forest. What does a total (161.816%) share in the structure of this forest. The results indicate that this forest contains a total volume of 2922,944 m3 for the entire area (158,662 ha). Capinurí (2021,071 m3), Capirona (699,380 m3), contain the highest volume values; on the contrary, Huimba (71,686 m3) and Lupuna (13,720 m3) present less volume. The species Capinurí (12,738 m3/Ha), Capirona (4,408 m3/Ha), report the highest volume per hectare; on the contrary, Huimba (0.452 m3/Ha) and Lupuna (0.086 m3/Ha) show lower volume per hectare. The general price of standing trees for the 5 species is S/ 611,660.15 and the price per hectare of the 5 forest species is S/ 3,855.11